Efektivitas Undang-Undang Nomor 33 Tahun 2014 Tentang Jaminan Produk Halal Dalam Perlindungan Konsumen - Fajaruddin Fajaruddin (Universitas Muhammadiyah Sumatera Utara, 2018)
Law No. 8 of 1999 concerning Consumer Protection provides protection for consumer rights. Among these protections is the necessity of halal labels on every food and beverage product. Violation of halal labeling is a mistake made by businesses against the inclusion of halal labels in the publishing of products and services. In fact there are still many food and beverage products that use illegitimate ingredients, or in other words there are still many food and beverage products that are still in crisis from halal. The Law No. 33 of 2014 Concerning Halal Product Guarantee Law is a refinement of the law which previously regulated the necessity for halal smelting. This law is expected to be a more perfect rule in protecting consumers from illicit products.